Introduction to philosophy : classical and contemporary readings - Perry, John, 1943-; Bratman, Michael (New York ; Oxford : Oxford University Press, 1999)
This is the third edition of an anthology intended for an introductory philosophy course. It is a comprehensive, topically organised anthology of both classical and contemporary philosophy.
Previous ed.: 1993.
Keywords: Philosophy; Philosophy